ئاستی گرنگیدانی میدیای کوردی بهکهسایهتی سیاسی و سهردانهکهی مستهفا کازمی بۆ ههرێمی کوردستان ههواڵهکانی کاتژمێر (٨(ی ههردوو تهلهفزیۆنی(K24, NRT (بهنموونه - حهمه, یوهان عوسمان (Sulaimani Journal for Humanities, 2021)
In many societies, and especially in the Middle East, television media tools are an important source for information and news, although the new media is close to declining and reducing the impact of television, due to the high cost of new media and the low cost of television. The lack of internet technology services in all cities and villages of Kurdistan are another reason for the importance of watching to television, have access to get information and meeting the demands of the masses. (Kurdish Televisions, Kurdish News, News of Kurdish Politician, PM Mustafa Kazmi, Kurdistan Region, Mustafa Kazmi Trip to Kurdistan, Iraq Federal Government & Kurdish Government )